Long-term Evolution of Protostellar and Protoplanetary Disks. II. Layered Accretion with Infall - Zhu, Zhaohuan; Hartmann, Lee; Gammie, Charles (arXiv.org, 2010)
We use one-dimensional two-zone time-dependent accretion disk models to study the long-term evolution of protostellar disks subject to mass addition from the collapse of a rotating cloud core. Our model consists of a constant surface density magnetically coupled active layer, with transport and dissipation in inactive regions only via gravitational instability. We start our simulations after a central protostar has formed, containing ~ 10% of the mass of the protostellar cloud. Subsequent evolution depends on the angular momentum of the accreting envelope. We find that disk accretion matches the infall rate early in the disk evolution because much of the inner disk is hot enough to couple to the magnetic field. Later infall reaches the disk beyond ~10 AU, and the disk undergoes outbursts of accretion in FU Ori-like events as described in Zhu et al. 2009c. If the initial cloud core is moderately rotating most of the central star's mass is built up by these outburst events. Our results suggest that the protostellar "luminosity problem" is eased by accretion during these FU Ori-like outbursts. After infall stops the disk enters the T Tauri phase. An outer, viscously evolving disk has structure that is in reasonable agreement with recent submillimeter studies and its surface density evolves from \(Σ \propto R^{-1}\) to \(R^{-1.5}\). An inner, massive belt of material-- the "dead zone" -- would not have been observed yet but should be seen in future high angular resolution observations by EVLA and ALMA. This high surface density belt is a generic consequence of low angular momentum transport efficiency at radii where the disk is magnetically decoupled, and would strongly affect planet formation and migration.